Financial Analysis Through The Application of Green Growth Economy (GGE) As A Moderation Variable Affects The Increase In GDP / GNP Economic Income In Indonesia During The Covid-19 Period Towards The New Normal - Margaretha Prihatiningsih; Yusup Hari Subagyo; Vitalis Ari Widyaningsih (Journal Research of Social Science, Economics, and Management, 2022)
The study aims to determine whether the company's financial performance through financial ratio analysis and the application of GGE (Green Growth Economy) as a moderation variable affects the increase in GDP / GNP economic income during the Covid-19 period towards the New Normal can be achieved properly. The population in the study was 36 Main Board Companies in the Property and Real-Estate Sub-Sector, a sample of 17 companies with a purpose sampling method. Multiple Correlation Regression Analysis Method with t TEST and F TEST and Classical Assumption Test using SEM Analysis Model (Structure Equation Model) & MRA Test (Moderating Regression Analyze). Based on the Results of the Analysis of Mediation Tests With MRA Regression (Moderating Regression Analyze), Cash Ratio, NPM with a significance value of 0.386 & 0.244 greater than 0.05 Then indirectly through GGE is not able to affect GDP / GNP which means it is rejected. Meanwhile, DER and ROA with a significance value of 0.016 & 0.042 are able to affect GDP / GNP. Likewise, DER & ROE with significance values of 0.002 & 0.007 < 0.05 Then indirectly through GGE is able to affect GDP / GNP. CAR, NPM through GGE with significance values of 0.538, 0.171 > 0.05 Then it is not able to affect GDP/GNP which means it is rejected. While DER & ROA through GGE as a moderation variable with a significance value of 0.029 & 0.016 is indirectly able to affect GDP / GNP. DER, ROE, NPM via GGE as moderation variables with a significance value of 0.038; 0,002; 0.046 < 0.05 Then it can affect GDP/GNP. Sedankan Cash, DAR, NPM via GGE as moderation variables with significance values 0.196;0.193; 0.535 > 0.05 Then it is not able to affect GNP/GDP which means it is rejected.